Formulation of survival acceptor medium able to maintain the viability of skin explants over in vitro dermal experiments. (11th November 2019) - Tarnowska, M.; Briançon, S.; de Azevedo, J. Resende; Chevalier, Y.; Barratier, C.; Pourcher, T.; Bolzinger, M.‐A.
Abstract: Objective: In vitro assessments of skin absorption of xenobiotics are essential for toxicological evaluations and bioavailability studies of cosmetic and pharmaceutical ingredients. Since skin metabolism can greatly contribute to xenobiotic absorption, experiments need to be performed with skin explants kept viable in suitable survival media. Existing protocols for non‐viable skin are modified to consider those conditions. The objective was to design a survival medium used as an acceptor fluid in Franz cells for testing cutaneous penetration of hydrophilic or lipophilic molecules. Their metabolism inside skin may be investigated under the same conditions. The determining factors involved in survival mechanisms in vitro are discussed. The consequences of short‐term skin preservation at 4°C were also evaluated. Methods: The metabolic activity of fresh skin samples mounted in Franz cells was studied by measurement of lactate release over 24 h in order to assess the impacts of pH, buffering, osmolality, ionic strength, initial glucose supply and the addition of ethanol or non‐ionic surfactant in the acceptor part of Franz cells. Conclusion: Survival media must maintain physiological pH (>5.5) be isotonic with skin cells (300 mOsm kg −1 ) and contain at least 0.5 g L −1 glucose. Several compositions able to preserve skin metabolism are reported. Storage of skin explants overnight at 4°C impairs skin metabolic activity. The present work provides guidelines for designing survival media according to constraints related to the scientific requirements of the experiments. Résumé: Objectifs: Les études d'absorption cutanée sont indispensables pour les évaluations toxicologiques et les études de biodisponibilité des ingrédients cosmétiques et pharmaceutiques. Etant donné que le métabolisme cutané peut contribuer à l'absorption cutanée des xénobiotiques, les études doivent être parfois menées sur les explants cutanés maintenus en survie à l'aide d'un milieu adapté. Les protocoles classiques utilisés avec des explants congelés non viables sont souvent modifiés pour prendre en compte ces conditions particulières. L'objectif de cette étude est d'étudier les conditions nécessaires à appliquer au milieu receveur des cellules de Franz pour maintenir la viabilité des explants, dans les études de pénétration cutanée de molécules hydrophiles et lipophiles. Leur métabolisme dans la peau peut être étudié dans ces mêmes conditions. Les facteurs déterminants à prendre en compte pour assurer la viabilité des explants in vitro sont discutés. Les conséquences de la conservation des explants cutanés durant une courte durée à 4°C, avant utilisation, ont été également évaluées. Methodes: L'activité métabolique des échantillons de peau, montés en cellules de Franz, a été évaluée grâce aux mesures du lactate produit durant 24h, durée de l'expérience. L'impact du pH, de solutions « tampon », de l'osmolalité, de la force ionique, de la concentration initiale en glucose et de l'addition d'éthanol ou de tensioactifs non‐ioniques, dans le milieu receveur de la cellule de Franz, a été étudié. Conclusion: Le milieu de survie doit maintenir un pH physiologique (>5.5), être isotonique par rapport aux cellules de la peau (300 mOsm kg ‐1 ) et contenir au moins 0.5 g L ‐1 de glucose. Plusieurs compositions capables de maintenir le métabolisme cutané sont décrites. La conservation des explants cutanés à 4°C, durant une nuit, perturbe l'activité métabolique de la peau. Ces travaux permettent de mettre en évidence des prérequis pour la formulation de milieux de survie adaptés aux expériences.